Media Pembelajaran Matematika dengan Materi Bangun Datar dan Bangun Ruang Berbasis Web - Lalu Puji Indra Kharisma; Yunita Happy Yana (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2021)
Mathematics lessons at the elementary level in the opinion of most students are still considered difficult because of the large number of calculation formulas that must be learned and use logic in analyzing and completing calculations. The learning model currently applied is the lecture learning model by means of one-way communication where the educator is active while the students only function their senses of sight and hearing. The conventional learning model mentioned above is considered to be less exploring students' knowledge insights during the teaching and learning process. If the student's concentration is less than optimal, then the student will have difficulty accepting the material being taught at that time, especially mathematics lessons with material two-dimentional figure and geometry, considering that the material must be systematic and requires a lot of practice questions to deepen mathematical concepts and problems. Therefore, mathematics is not enough to just be studied in class. Students must learn independently outside the classroom. So that we need a media that can help students in learning outside the classroom. With the current development of information technology, especially in terms of internet use, it has an impact on changes in learning system patterns, This change in the pattern of the learning system makes the learning process more creative because learning resources are not only carried out from inside the classroom but can be done outside the classroom and discussed in the classroom together. This is the impact of the rapid development of internet technology. Therefore, the author aims to create a mathematics learning media with material two-dimentional figure and geometry web-based for elementary schools.